Immigrant latin american workers as elderly home caregivers - Juana Robledo Martín; Mª Cristina Martín-Crespo Blanco; Ana Belén Salamanca Castro (Fundación para el Desarrollo de la Enfermería, 2008)
Informal care of elderly people is related to gender, generation and cultural aspects. However, the important social, demographic and economical changes that have happened in Spain, have made that it has increased the difficulty to conciliate the caregiver role with other social ones, causing, as a consequence, a progressive decrease of the informal resource, that is known as " the informal caregiver crisis". So, immigration is helping to keep the maintenance of informal caregivers in Spain. In this study we will explore the interaction among immigrant Latin American workers as elderly caregivers in Madrid and the old person and the elderly families. A qualitative methodology will be used, developing interviews and participant observation. The study population will be composed by immigrant Latin American women who work as home caregivers of elderly dependent people that must have been living in Spain more than two years, the elderly who received their cares and their families. Data analysis will be made throughout the investigation process, using the support of the software Atlas Ti 5.0 for the discourse analysis. Results will be shared with immigrant community groups, health care professionals and scientific journals.